2022
DOI: 10.3982/ecta18583
|View full text |Cite
|
Sign up to set email alerts
|

Detecting p‐Hacking

Abstract: We theoretically analyze the problem of testing for p‐hacking based on distributions of p‐values across multiple studies. We provide general results for when such distributions have testable restrictions (are non‐increasing) under the null of no p‐hacking. We find novel additional testable restrictions for p‐values based on t‐tests. Specifically, the shape of the power functions results in both complete monotonicity as well as bounds on the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 35 publications
1
52
0
Order By: Relevance
“…With forking paths, we should not be interested in p-hacking tests such as the ones in Elliott et al (2022) because the purpose of exhaustive paths is precisely to avoid p-hacking in the first place. However, out of curiosity and in full disclosure, we have used these tests on the series of paths obtained from our two empirical studies and got disappointing results: while we did not hack, the tests in some cases concluded that we did.…”
Section: Discussion On P-hacking Testsmentioning
confidence: 99%
See 4 more Smart Citations
“…With forking paths, we should not be interested in p-hacking tests such as the ones in Elliott et al (2022) because the purpose of exhaustive paths is precisely to avoid p-hacking in the first place. However, out of curiosity and in full disclosure, we have used these tests on the series of paths obtained from our two empirical studies and got disappointing results: while we did not hack, the tests in some cases concluded that we did.…”
Section: Discussion On P-hacking Testsmentioning
confidence: 99%
“…In Elliott et al (2022), there are 3 important distributions: F h , the one of the test statistic, F the distribution that determines the critical values under the null, and Π, the true distribution of the effect under scrutiny. The latter does not matter, as all tests in Elliott et al (2022) hold irrespective of Π. Critical values are also rarely an issue, as they are often determined based on standard asymptotic results.…”
Section: Discussion On P-hacking Testsmentioning
confidence: 99%
See 3 more Smart Citations